PENGARUH PEMBIAYAAN MURABAHAH DAN PEMBIAYAAN IJARAH MULTIJASA T ERHADAP PROFITABILITAS BPRS PATRIOT BEKASI - MUFID HABIB MUSTOFA; GIVI EFGIVIA; NUR RAHMI ALFATH (DIRHAM Jurnal Ekonomi Islam, 2020)
BPRS (Bank Pembiayaan Rakyat Syariah Patriot Bekasi is financial institution thatdistribute and collect the fund. Bank Pembiayaan Rakyat Syariah Patriot Bekasiprefers to provide in micro, small and medium enterprises. The purpose of this study is to analyze the effect of financial in Bank Pembiayaan Rakyat Syariah Patriot Bekasi, Murabahah, Ijarah multijasa, on profitability of the Bank Pembiayaan Rakyat Syariah Patriot Bekasi. This research uses quantitative methods with secondary data. The data collection techniques used are literature study and documentation secondary data retrieved from monthly reports of statistical perbankan syariah which can be accessed through the official website of OJK and BI. The result of research using secondary data noted there if F-3,3550 smaller and ijarah multijasa have no effect on profitability PT Bank Pembiayaan Rakyat Syariah Patriot Bekasi, with R2of 50,40% and the remaining 49,6% is affected by other products.Keywords :Murabahah, Ijarah Multijasa, Profitabilitas, Bank Pembiayaan RakyatSyariah Patriot Bekasi